The Influence of Personality Traits and Job Characteristics on Work Motivation and Job Performance in the Hospitality Industry in Indonesia - Irdhayanti, Efa; Marditama, Theresia; Syafri, Muhammad; Mokodenseho, Sabil; Purwoko , Bambang (Eastasouth Institute, 2024)
This research investigates the intricate relationships among personality traits, job characteristics, work motivation, and job performance within the context of the Indonesian hospitality industry. Utilizing a sample of 220 participants, a robust structural equation model was developed and tested. The model demonstrated excellent fit indices, reinforcing its effectiveness in capturing the complexities of the variables under scrutiny. Hypothesis testing revealed significant positive relationships between job characteristics and both job performance and work motivation, as well as between personality traits and job performance and work motivation. The model's high explanatory power (R²) and predictive relevance (Q²) underscore its utility in understanding and forecasting outcomes in the studied industry. The findings offer valuable insights for organizational practitioners aiming to optimize employee performance and motivation in the dynamic landscape of the Indonesian hospitality sector.